Detecting Upward Directed Charged Particle Fluxes in the Mars Science Laboratory Radiation Assessment Detector. Issue 1 (23rd January 2018) - Appel, J. K.; Köehler, J.; Guo, J.; Ehresmann, B.; Zeitlin, C.; Matthiä, D.; Lohf, H.; Wimmer‐Schweingruber, R. F.; Hassler, D.; Brinza, D. E.; Böhm, E.; Böttcher, S.; et al.
Abstract : The Mars Science Laboratory rover Curiosity, operating on the surface of Mars, is exposed to radiation fluxes from above and below. Galactic Cosmic Rays travel through the Martian atmosphere, producing a modified spectrum consisting of both primary and secondary particles at ground level. These particles produce an upward directed secondary particle spectrum as they interact with the Martian soil. Here we develop a method to distinguish the upward and downward directed particle fluxes in the Radiation Assessment Detector (RAD) instrument, verify it using data taken during the cruise to Mars, and apply it to data taken on the Martian surface. We use a combination of Geant4 and Planetocosmics modeling to find discrimination criteria for the flux directions. After developing models of the cruise phase and surface shielding conditions, we compare model‐predicted values for the ratio of upward to downward flux with those found in RAD observation data. Given the quality of available information on Mars Science Laboratory spacecraft and rover composition, we find generally reasonable agreement between our models and RAD observation data. This demonstrates the feasibility of the method developed and tested here. We additionally note that the method can also be used to extend the measurement range and capabilities of the RAD instrument to higher energies. Plain Language Summary: The MSL rover Curiosity is exposed to energetic particles from above and below on the Martian surface. Particles enter the Martian atmosphere from above and travel through it until they reach the ground. Particles lose energy and can produce secondary particles while passing through the atmosphere, resulting in an energy distribution on ground level that is different from that on the top of the atmosphere. The resulting particles produce an upward directed particle distribution in the soil. We develop a method to distinguish the upward and downward particle fluxes in the RAD instrument, verify it using data taken during the cruise to Mars, and apply it to data taken on the Martian surface. We use a combination of models to find criteria for discriminating the flux directions. After developing models of the cruise phase and surface shielding conditions, we compare simulated values for the ratio of upward to downward flux with those found in observation data. We find generally reasonable agreement between our models and RAD observation data. This demonstrates the feasibility of the method developed and tested here. The method can also be used to extend the measurement range and capabilities of the RAD instrument to higher energies. Key Points: We model the radiation environment during the MSL cruise phase and on the Martian surface We obtain the particle energy spectra at the RAD instrument for both scenarios After developing a method to distinguish between upward and downward fluxes, we apply the method both to simulation data and to data taken by the RAD instrument during the cruise phase and on the surface